Condensation heat transfer characteristics of R-134a flowing inside the multiport minichannels - Sakamatapan, Kittipong; Kaew-On, Jatuporn; Dalkilic, Ahmet Selim; Mahian, Omid; Wongwises, Somchai (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
In this study, the condensation heat transfer characteristics of R-134a flowing inside multiport minichannels were investigated. The multiport minichannel-tested tubes have 14 channels with a 1.1 mm hydraulic diameter, and eight channels with a 1.2 mm hydraulic diameter were designed as a counterflow tube-in-tube heat exchanger. The experiment was performed with mass fluxes of refrigerant between 340 and 680 kg/m(2)s, with 15, 20, and 25 kW/m(2) heat fluxes, and saturation temperatures of 35-45 degrees C. The flow pattern for the experimental data was initially predicted using existing flow pattern maps. It could be noted that the annular flow pattern existed for most of the experimental data. Results showed that the average heat transfer coefficient increased with the increase of vapor quality, mass flux, and heat flux, but decreased as saturation temperature rose. When compared with two correlations obtained from condensation inside the multiport minichannels, the heat transfer coefficient could be predicted within an acceptable range. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Condensation; Heat transfer characteristics; R-134a; Multiport minichannels; MICRO-FINS; DIAMETER TUBES; PRESSURE-DROP; R134A; REFRIGERANTS; TRANSITION; Thermodynamics; Engineering; Mechanics